Total Edge Irregularity Strength of Graph L_3⊙N_m - Nikita; Sri Nurhayati; Trisha Magdalena A. Jauvani; Selvy Musdalifah; Iman Al Fajri; Andri (Program Studi Pendidikan Matematika Universitas Katolik Santo Agustinus Hippo, 2025)
An edge irregular total k-labeling of a simple graph is a labeling that assigns positive integers to its vertices and edges such that the weight of every edge, defined as the sum of the labels of the edge and its two incident vertices, is distinct. The smallest integer that allows such a labeling is called the total edge irregularity strength, denoted by In this paper, we study the total edge irregularity strength of the corona product of a ladder graph ​ and a null graph ​, denoted by By applying constructive labeling and analyzing the resulting edge weights, we show that all edges can be assigned distinct weights. From Theorem 1, it is obtained that . This result contributes to the development of graph labeling theory and can be extended to larger ladder graphs for further applications, including cryptography and network security.